feedback to promote speaking skill - Bouhalili, Hanan (My University, 2020)
Feedback and reflective thinking are two major important factors that contribute to ones’ own learning and improve it. However, to enhance learners' reflective thinking and give and receive feedback in a good and effective way, one may need to use different tools to facilitate and help students and teachers during the learning process. An example of such tools is the use of reflective work sheets. This study aims at investigating the role of the reflective work sheet in enhancing teachers' reflective feedback to promote speaking skill. Furthermore, the present research attempts to present for students and teachers a new tool, which is the reflective work sheet, to better understand and find solutions to students' errors. In conducting this research, a mixture of qualitative and quantitative methods was used to collect data from the respondents which are questionnaire and interview to prove or disconfirm the research hypothesis. This study was conducted with second year Master students of didactics of foreign languages at Abdelhamid Ibn Badis University. The results enquire that feedback and reflective thinking are two essential elements to develop students' speaking skills and help them overcome their errors. On the other hand, reflective work sheets can be a good choice for both teachers and students to use in their regular reflections to more improve and develop their speaking proficiency and the learning experience in its entirety.
Case study of Second Year Master students at AbdelHamid Ibn Badis University in Mostaganem
Keywords: Reflective thinking; Reflective work sheets; Feedback; Speaking skill